Importance of infragravity waves in a wave-dominated inlet under storm conditions. (1st January 2020) - Mendes, Diogo; Fortunato, André B.; Bertin, Xavier; Martins, Kévin; Lavaud, Laura; Nobre Silva, Ana; Pires-Silva, António A.; Coulombier, Thibault; Pinto, José P.
Abstract: The processes associated with infragravity waves (IGW) and their role on the hydro-sedimentary dynamics of a wave-dominated inlet are investigated using field observations collected at the Albufeira Lagoon (Portugal) during storm Leslie in October 2018. During the storm, significant IGW heights reached up to 1.0 m in the surf zone and 0.4 m inside the lagoon. IGW frequencies were blocked by ebb currents at the flood-delta and this effect was stronger for higher IGW frequencies. Therefore, low-frequency IGW were able to propagate further into the inner lagoon. The application of a 1D energy balance equation suggests that depth-induced breaking and bottom friction contributed equally to dissipate IGW energy at the flood-delta and that this dissipation was stronger during the flood than during the ebb. Large horizontal velocities under IGW crests increased the instantaneous suspended sediment transport rate by up to two orders of magnitude during flood at the flood-delta. The net suspended sediment transport rate and its variability, associated with the wave motion, was positive (landward) during flood and negligible during ebb. These positive values were associated with large wave-induced orbital velocities, suggesting that waves were more effective than tidal currents in inducing suspended sediment transport. The oscillatory suspended sediment transport rate was directed towards the lagoon and dominated by IGW frequencies. The observed sediment accretion of the northern channel occurred during the most energetic IGW. The measurements presented in this study and their analyses demonstrate how IGW play a major role in the sedimentary dynamics of wave-dominated inlets during storm conditions. Highlights: Water levels, velocities, sediment concentrations and topography measured in a wave-dominated inlet under storm conditions. Ebb currents blocked high infragravity wave (IGW) frequencies and low IGW frequencies were able to propagate into the lagoon. Suspended sediment transport and its variability were dominated by IGW frequencies. The net sediment transport was landward during flood and negligible during ebb. Sediment accretion of the inlet's north channel coincided with the most energetic IGW.